Modulation of Phytohormone Signaling: A Primary Function of Flavonoids in Plant–Environment Interactions - Brunetti, Cecilia; Fini, Alessio; Sebastiani, Federico; Gori, Antonella; Tattini, Massimiliano (Frontiers in Plant Science, 2018)
The old observation that plants preferentially synthesize flavonoids with respect to the wide range of phenylpropanoid structures when exposed to high doses of UV-B radiation has supported the view that flavonoids are primarily involved in absorbing the shortest solar wavelengths in photoprotection. However, the biosynthesis of flavonoids is similarly upregulated in response to high photosynthetic active radiation in the presence or in the absence of UV-radiation, as well as in response to excess photosynthetic redox unbalance. This recent evidences support the hypothesis that flavonoids may play prominent roles as scavengers of reactive oxygen species (ROS) generated by light excess. These ‘antioxidant’ functions of flavonoids appears robust, as maintained between different life kingdoms, e.g., plants and animals. The ability of flavonoids to buffer stress-induced large alterations in ROS homeostasis is at the base of long-reported functions of flavonoids as developmental regulators in both plants and animals. Indeed, there is long evidence that, in plants, flavonoids may strongly affect phytohormone signaling, e.g. auxin and abscisic acid signaling. This function is served by flavonoids in a very low (nM) concentration range and involves the ability of flavonoids to inhibit the activity of a wide range of protein kinases, including but not limited to mitogen activated protein kinases, that operate downstream of ROS in the regulation of cell growth and differentiation. Flavonoids inhibit the transport of auxin acting on serine-threonine PINOID (PID) kinases and may also regulate auxin gradients at cellular and tissue levels, by reducing auxin catabolism, with consequences on developmental processes. Recent observations lead to hypothesize that regulation/modulation of auxin transport/signaling likely represents the ancestral function of flavonoids. The antagonistic functions of flavonoids on ABA-induced stomatal closure also offer novel hypotheses on the functional role of flavonoids in plant-environment interactions, in early as well as in modern terrestrial plants. We hypothesize that the regulation of phytohormone signaling likely represented the primary function served by flavonols for the conquest of land by plants and it is still of major significance for the successful acclimation of modern terrestrial plants to a severe excess of radiant energy.